Apr``ès la pandémie : Transformations des villes, du travail, et la crise climatique - Mirza, Vincent (Anthropologica, 2021)
This article aims to discuss, in the context of the pandemic, the relationship between the climate crisis, transformations of work, and the reorganization of cities. It is based on the idea that the pandemic is a result of the climate crisis whose end cannot be envisioned without reconfiguring urban spaces and rethinking inequalities in order to think about different social forms that reconcile green, healthy, and more egalitarian cities.